Effect of titanium-doped bioactive glass on poly(2-hydroxyethyl methacrylate) hydrogel composites: Bioactivity, intermediate water, cell proliferation, and adhesion force. (1st May 2023) - Mabrouk, Mostafa; Beherei, Hanan H.; Shiomoto, Shohei; Tanaka, Yukiko; Osama, Lamyaa; Tanaka, Masaru
Abstract: The intermediate water (IW) concept has been hypothesized to predict the biocompatibility of polymers and inorganic materials. This study, for the first time, prepared the composite biomaterials of poly(2-hydroxyethyl methacrylate) (PHEMA)/titanium-doped bioactive glasses (BGT) for bone regeneration by applying the IW concept. The homogeneous distribution of BGT and the mechanical stability of the composites were confirmed using X-ray diffraction, infrared spectroscopy, scanning electron microscopy, energy dispersive X-ray spectrometry, and rheological characterization. In vitro tests with immersion in simulated body fluid showed that titanium doping improved the biomineralization properties. The IW level ranged from 10.4 wt% with 0% titanium doped to 25.6 wt% with 7.5% titanium doped. Cell viability tests on osteosarcoma cells revealed that the growth rate increased with increasing titanium concentration, reaching up to 150%. Based on single-cell force spectroscopy, an appropriate titanium concentration for cell adhesion was estimated to be 5%. The hydrated PHEMA gels with 5% BGT exhibited a high IW level of 19.3% and less hydrophilic wettability than the gels without titanium or with 10% BGT. The IW concept proved to be useful for predicting the bone regeneration potential on the interfaces of the PHEMA/BGT composite hydrogels.